Elaboración de un sistema de calidad HACCP mediante un diagnóstico funcional en el área de producción de la empresa Sumerco S.A. - Cobo García, Carlos Alfredo (2016)
This research aimed to develop a quality HACCP by a functional diagnosis in the production area Sumerco SA, to carry out made use of various instruments of evaluations, first a form of verification of compliance with GMP applied whose unsatisfactory results were globally as defaults with 63% of evaluated parameters; subsequently the Delphi method which was based on three qualitative questions asked staff to then evaluate the results by three times in the last of these responses could be converted into quantitative where each result was tabulated using the Pareto chart was applied; Once completed the stage of functional diagnosis was achieved develop the HACCP plan process line so that the line of sausages two PCs one identified at the stage of receiving raw material and another in the phase cutterizado and himself they identified two PCC, one at step smoked and another in storage, while the PCC identified in the line of cuts of meat is the step of receiving M.P.